The Effect of Third Party Funds, Loans Disbursed, and Allowance for Impairment Losses on Stock Prices: Empirical Study on Conventional Banking Companies Listed on the Indonesia Stock Exchange for the 2023–2025 Period - Venni Avionita; Rizke Wiliyanti; Rediawan Miharja; Rabhi Fathan Muhammad (LP2M IAIN Palopo, 2026)
This study aims to analyze the effect of Third Party Funds (DPK), Loans Disbursed, and Allowance for Impairment Losses (CKPN) on Stock Prices of conventional banking companies listed on the Indonesia Stock Exchange for the period 2023–2025. The study is motivated by the empirical phenomenon of declining banking stock prices concurrent with increasing net income, indicating that investor decision making is not exclusively driven by profitability considerations, but also encompasses fund mobilization, credit disbursement, and credit risk management practices. This study employs a quantitative approach with panel data regression analysis. The sample was determined using purposive sampling, yielding 39 banking companies with a total of 117 observations over the study period. Data analysis was conducted using EViews 12, encompassing descriptive statistics, classical assumption tests, panel data model selection, and hypothesis testing using the Random Effect Model (REM). The results indicate that Third Party Funds, Loans Disbursed, and CKPN jointly exert a significant effect on Stock Price. On a partial basis, Third Party Funds exert a positive and significant effect on Stock Price; Loans Disbursed do not exert a significant effect on Stock Price; and CKPN exerts a positive and significant effect on Stock Price. These findings are consistent with Signaling Theory, which posits that information relating to fund mobilization and credit risk management constitutes an important signal for investors in assessing banking company prospects. This study, therefore, demonstrates that investors do not assess banking companies solely based on profitability, but also consider the bank's capacity to mobilize public funds and manage credit risk effectively as foundational considerations in investment decision making. Keywords: Stock Price, Third Party Funds, Loans Disbursed, Allowance for Impairment Losses.